1986
DOI: 10.1148/radiology.158.2.3941873
|View full text |Cite
|
Sign up to set email alerts
|

Cricoarytenoiditis: CT assessment in rheumatoid arthritis.

Abstract: The cricoarytenoid (CA) joint is a true diarthrodial joint that can be affected by rheumatoid disease. Its strategic location in the airway anatomy makes its evaluation of clinical importance. Direct fiberoptic laryngoscopy (DFL) and high-resolution computerized tomography (HRCT) were used to assess the larynx in 32 rheumatoid patients. Abnormalities were seen in 75% of patients at endoscopic examination. HRCT studies showed abnormalities in 72%. Erosion-luxation of the CA joint and surrounding soft-tissue swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…11 Since then, there have been several studies that have demonstrated a high prevalence of laryngeal abnormalities in patients with RA, with the incidence being higher in females compared with males. [1][2][3][4][5][6][7][8][9][10][11][12] Most reports on laryngeal involvement in RA patients have focused on the CAJ because of the prevailing increase in incidence and the subsequent serious clinical implications. Acute laryngeal involvement can cause swelling of the vocal folds with airway obstruction, and chronic involvement can impair vocal fold mobility with resultant fixation and narrowing of the glottis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Since then, there have been several studies that have demonstrated a high prevalence of laryngeal abnormalities in patients with RA, with the incidence being higher in females compared with males. [1][2][3][4][5][6][7][8][9][10][11][12] Most reports on laryngeal involvement in RA patients have focused on the CAJ because of the prevailing increase in incidence and the subsequent serious clinical implications. Acute laryngeal involvement can cause swelling of the vocal folds with airway obstruction, and chronic involvement can impair vocal fold mobility with resultant fixation and narrowing of the glottis.…”
Section: Discussionmentioning
confidence: 99%
“…On CT scanning, the prevalence of CAJ abnormalities vary between 54% and 72%. 7 The most commonly reported findings include cricoarytenoid prominence (46.6%), density and volume changes in the CAJ (46.6%), sublaxation (39.9%), decrease in the CAJ space (13.3%), narrowing in the piriform sinuses (33.3%), and irregularities in the contour of the CA joint (20%). Erosion and ankylosis seem to be less common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Radiologic evaluation using low-voltage neck radiography and computed tomography can also be diagnostic. 1,19 Treatment of rheumatoid cricoarytenoid arthritis involves management of the systemic disease. 9 Acute stage therapy includes voice rest, local heat, antiinflammatory medication and steroids.…”
Section: Objectif : Présenter Un Cas D'obstruction Des Voies Respiratmentioning
confidence: 99%
“…Any synovial surface in the body can be affected and females are in the majority. [1][2][3] Comprehensive assessment of the potential hazards facilitates careful anesthetic management. [2][3][4] We report a case of acute upper airway obstruction due to cricoarytenoid arthritis, a well-known but rare complication of rheumatoid arthritis.…”
mentioning
confidence: 99%